(untitled) (Research, Society and Development, 2022)
The teaching-learning method in Nursing Residency, used in in-service specialization, is of fundamental importance in the process of training nurses, and their technical-scientific and ethical development. The general objective of the study is to discuss the teaching-learning methods of the specialization courses in the form of in-service training along the lines of Nursing Residencies, based on scientific publications, and their aspects of importance for professional training. This is an Integrative Literature Review study carried out in the LILACS and SciELO electronic library databases, which directly and indirectly address the teaching-learning process in Nursing Residencies. The Descriptors of Health Sciences (DeCS), nursing education, nursing and internship and residency were used for the electronic search of the articles, connected by the Boolean operator AND. 90 texts were found, of these 9 were selected and analyzed. As a result, the usual teaching-learning methods in nursing residency and their important factors for professional training are discussed. The experience of the preceptor and the resident nurse on the teaching-learning process stands out. A reflection on the academic theory and practice of the professional is proposed, based on the training and qualification obtained and developed in the teaching-learning process, contributing so that newly graduated nurses have access to information about the nursing residency, its teaching model- learning and its importance for professional training.